Modeling of solid-liquid flow inside conical diverging sections using computational fluid dynamics approach - Singh, Harmanpreet; Kumar, Satish; Mohapatra, Saroj Kumar (International journal of mechanical sciences, 2020)
•Flow separation is observed in short diverging sections.•The separation length is found to be a strong inverse function of Reynold's number.•The flow reattaches on slight increase in the section length.•Increasing section length experiences decreasing velocity gradient and increasing skin friction.•The section that balanced velocity gradient and skin friction yielded minimum pressure loss and maximum pressure recovery. In a slurry pipeline, the diverging sections are an important pipe fitting and also a cause of major pressure loss and sometimes flow separation. To address this potential issue, the complex solid-liquid flow of coal water slurry through conical diverging sections is simulated using the computational fluid dynamics approach. Nine different geometries of the diverging sections are analyzed in the present study. The length of the diverging section is the key variable in the geometric variations and ranges from 0.05 m to 0.6 m. The influx velocity at the entrance of all the diverging sections is varied in the range of 0.5 m/s to 5 m/s. The mass concentration of the solids dispersed inside the liquid phase is varied from 10 to 60%. The results generated by the computational fluid dynamics tool are in good agreement with the experimental data. The design of the diverging section is evaluated based on results obtained for three characterization parameters viz. pressure recovery coefficient, head-loss across the diverging section and volumetric efficiency. The 0.3 m long diverging section is found to be the optimum design for best pressure recovery, maximum volumetric efficiency and lowest head-loss. [Display omitted]